2007
DOI: 10.1179/174329307x164283
|View full text |Cite
|
Sign up to set email alerts
|

Plasma augmented laser welding of 6 mm steel plate

Abstract: A hybrid laser arc welding system incorporating a plasma arc in a triangulated configuration (plasma augmented laser welding -PALW) was used to produce bead on plate welds in 6 mm low carbon steel. Laser powers up to 5 kW and arc currents up to 150 A were investigated. Plasma augmented laser welding allowed an increase in full penetration welding speed of 100% or an increase in penetration of between 25 and 100%, compared with the laser alone. At speeds of 2 m min 21 and above, PALW and laser alone were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…The good ductility of the welded joints, even with no post-weld heat treatment, was highlighted by the ability to be bent successfully with progressively smaller former diameters. 4. Microstructural examination showed that the K-GTA welds were free from gross porosity and other defects, in agreement with the results of the radiographic testing.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The good ductility of the welded joints, even with no post-weld heat treatment, was highlighted by the ability to be bent successfully with progressively smaller former diameters. 4. Microstructural examination showed that the K-GTA welds were free from gross porosity and other defects, in agreement with the results of the radiographic testing.…”
Section: Discussionsupporting
confidence: 70%
“…For example, in recent work, Swanson et al were able to achieve full penetration welding of a 6 mm thick low carbon steel plate at a speed of 1 m min 21 , using a 4 kW CO 2 laser. 4 However, high capital cost, low efficiency and the need for excellent joint fit-up due to poor bridging capacity are significant disadvantages of this process. 4 More recently, there have been significant advances in hybrid laser arc welding processes.…”
Section: Introductionmentioning
confidence: 99%
“…One of its main advantages involves the ability to bridge gaps between workpieces in excess of that possible during laser welding. 19,[29][30][31][32][33][34][35] Finally, the combination of the laser and the arc in hybrid welding allows for the use of significantly higher welding velocities to achieve deeper penetrations than possible with arc welding alone. [36][37][38][39][40] This enhanced capability allows for full penetration welds to be achieved in a single pass, thus removing the need for additional passes.…”
Section: Introductionmentioning
confidence: 99%
“…(19) and (20), as given below, for gas temperature, K T , and density, K The thermodynamic state and velocity of the air on each side of the shock wave are related by the Rankine-Hugoniot relations, where the most convenient forms to this application are given by Eqs. (21) and (22). K M is the Mach number in the vapor, /2…”
Section: Laser-induced Recoil Pressure and Keyhole Dynamicsmentioning
confidence: 99%
“…1, hybrid laser-arc welding is formed by combining laser beam welding and arc welding. Due to the synergic action of laser beam and welding arc, hybrid welding offers many advantages over laser welding and arc welding alone [3][4][5][6] , such as high welding speed, deep penetration 7 , improved weld quality with reduced susceptibility to pores and cracks [8][9][10][11][12][13][14][15][16] , excellent gap bridging ability [17][18][19][20][21][22] , as well as good process stability and efficiency, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%